2012
DOI: 10.1016/j.jksus.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Earthquakes magnitude predication using artificial neural network in northern Red Sea area

Abstract: Since early ages, people tried to predicate earthquakes using simple observations such as strange or atypical animal behavior. In this paper, we study data collected from past earthquakes to give better forecasting for coming earthquakes. We propose the application of artificial intelligent predication system based on artificial neural network which can be used to predicate the magnitude of future earthquakes in northern Red Sea area including the Sinai Peninsula, the Gulf of Aqaba, and the Gulf of Suez. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 24 publications
0
46
0
1
Order By: Relevance
“…[5] proposed a method for the estimation of peak ground acceleration using ANN by taking inputs like magnitude, hypocentral distance and average shear wave velocity. [3] proposed a method using ANN to forecast earthquakes in northern Red Sea area. They presented different statistical methods and data fitting such as linear, quadratic and cubic regression.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…[5] proposed a method for the estimation of peak ground acceleration using ANN by taking inputs like magnitude, hypocentral distance and average shear wave velocity. [3] proposed a method using ANN to forecast earthquakes in northern Red Sea area. They presented different statistical methods and data fitting such as linear, quadratic and cubic regression.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The artificial neural networks (ANN) are one of the most accurate and widely used predicting models that have fruitful applications in many engineering problems [28,29]. The basics of ANN are presented in [28,29]; in addition, the application of ANN to predict the performance and damage detection of structures showed that the ANN is a good tool that can be used in this area [18,19]. Bigdeli and Kim [12] used ANN to predict the behavior of irregular buildingcontroller system under dynamic loads and found that the ANN can be used to identify the performance of building structures.…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…The total number of DOFs (42) after application of the boundary conditions (i.e., rigid diaphragm, Guyan reduction of vertical DOFs, and rotational DOFs around -and -axes) equals 9. The input signal generated artificially through shaking table [29] generates an acceleration signal having a waveform in which parameters such as strong motion duration, ramp times, and number of strong motion peaks are variables. The input and output signals generation and measurements are presented in [3,[31][32][33].…”
Section: Response Theory and Experimental Setupmentioning
confidence: 99%
“…Great eort was invested on the Parkeld prediction experiment [2]. The results obtained made the scientic community wonder if earthquakes could be predicted at all.…”
Section: Introductionmentioning
confidence: 99%